The Effects of El Nino Southern Oscillation on Rainfall in the Karst Area of Maros, National Park Bantimurung Bulusaraung South Sulawesi and its Impact on Flood Disasters - Muhammad Arsyad; Fitriani Fitriani; Vistarani Arini Tiwow; Pariabti Palloan; Sulistiawaty Sulistiawaty; Agus Susanto (Jurnal Ilmu Lingkungan, 2023)
The aims of this study were to describe rainfall profiles, to analyze the effect of the El Nino Southern Oscillation (ENSO) on rainfall and its impact on flood disasters in the karst area of Maros, National Park Bantimurung Bulusaraung South Sulawesi. The data used were monthly data of ENSO parameters and monthly data on rainfall of Karst Maros TN Babul area in the range of 2011-2020. The monthly data of ENSO parameters consist of Oceanic Nino Index (ONI) data, namely Nino Index 3.4 and Southern Oscillation Index (SOI) obtained from the official website of NOAA (National Oceanic and Atmospheric Administration) and from the official website of BOM (Bureau of Meteorology), respectively. Whereas, the monthly data of rainfall of Karst Maros TN Babul area was obtained from Maros Climatology Station, South Sulawesi. The data was analyzed (i.e. graph analysis and simple linear regression) using Microsoft Excel 2010 Software and ArcGIS Software for map creation. The results showed that the rainfall profile of the karst Maros TN Babul region for the period 2011-2020 has a monsoon rainfall pattern with the highest rainfall in December, January, and February, while the lowest rainfall occurs in June, July, and August. The significant effect of ENSO on rainfall in the Karst Maros TN Babul Area for the period 2011-2020 was categorized as a moderate with an ONI correlation coefficient value of 0.521 and SOI of 0.465. The effect of ENSO on rainfall is in the range from 25.9 to 33.1% which result in flood disasters in the karst Maros TN Babul area such as Bantimurung, Tompobulu, Camba, and Simbang districts. The flood disasters mostly occurs in January and December with rainfall intensity from high to very high category.